GAMBARAN PERILAKU CYBERBULLYING PADA REMAJA DI SMAN 9 PEKANBARU - Shinta Rahma Nata Sari; Fathra Annis Nauli; Wasisto Utomo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
The majority of internet users in Indonesia are adolescents aged 15-19 years makes traditional bullying transforms into cyberbullying. This study aims to determine the cyberbullying behavior of adolescents in Senior High School 9 Pekanbaru with descriptive quantitative design. The sample consisted of 250 respondents who were selected using proportional stratified random sampling technique. The Cyber Victim and Bullying Scale (CVBS) questionnaire is used to collect the data. The univariate analysis is used in this research. The results obtained that 54,8% (137 respondents) and 58% of adolescents (145 respondents) showed level of tendency of being cyberbullying perpetrators and victims in medium category. Cyberbullying action that is often done by respondents is cyberstalking which was 26,8% of adolescents (67 respondents). 32% adolescents (80 respondents) who had done cyberbullying claimed the reason was because they wanted to entertain themselves. In this study, it was found that all respondents had been both perpetrators and victims of cyberbullying. Based on the results of this study, it can be concluded that someone who is a perpetrators also has the opportunity to become a victim of cyberbullying. The reason why adolescents had done cyberbullying was because they wanted to entertain themselves shows the decreased in adolescent moral quality. The results of this study recommend the school to limit the used of gadgets by students in the school environment.Keywords: adolescents, CVBS (the Cyber Victim and Bullying Scale), cyberbullying behavior